A web-based system to manage elective waiting lists: efficiency and equity issues. (17th December 2009) - Testi, Angela; Tanfani, Elena; Valente, Roberto; Fato, Marco, Ivan Porro
Waiting lists for elective surgery are a topical issue in many publicly funded health systems. Decision makers should, therefore, state rules to prioritise access in order to attain both efficiency and equity. Efficiency requires that resources should be allocated to satisfy maximum social benefit. Equity means that everyone should receive healthcare at the right moment, i.e. before his/her conditions worsen (horizontal equity, depending on 'urgency'), and that different needs should receive different answers (vertical equity). In Italian National Health System since 2002 guidelines suggest classifying elective surgery referrals into categories (urgency-related groups, URGs) associated with a maximum waiting time within which the patient should receive treatment. The Surgical Waiting List Info System program is geared at setting and testing an experimental web-based informative system for prioritising elective surgery admissions belonging to different URGs and producing reports about the performance of waiting lists in terms of efficiency and equity indexes.